DESIGN AND SIMULATION HYBRID FILTER FOR 17 LEVEL MULTILEVEL INVERTER - Hutabarat, Marshal Andrea (Bulletin of Electrical Engineering and Informatics, 2019)
Increased use of renewable energy such as solar cells, wind power, ocean thermal and technology HVDC (high voltage direct current) causes an increase in the use of the inverter. Harmonics that generated by the inverter has a negative impact on the electrical equipment, it can cause excessive heat and may shorten the life of electrical equipment. A multilevel inverter is an arranged in a stack of several inverters in cascaded form which it aims to reduce THD (total harmonic distortion). In this work, the designed 17 levels of a single phase cascaded multilevel inverteris proposed. With the aid of PSIM, the THD of this inverter were compared to THD produced by single pulse width modulation (SPWM) inverter and the hybrid filter to reduce its THD also proposed. The results show that the THD produced by cascaded multilevel inverter much smaller than SPWM one. The increasing of load tend to cause the THD values also increased. Therefore, it is a requirement to install the filters to reduce the value of THD to comply it with IEEE 519-2014 standard. Installation of hybrid filter able to fix a maximum of 0.23% THDv and a maximum of 1.05% THDi.